Vegetation-environment relationships in the Akdağ (Burdur) region (Journal of Forestry, 2024)
In this study, the distribution of woody vegetation and the characteristics of the growing environment in the Akdağ (Burdur) region were determined, and forest site classification was established. Fieldwork was conducted on 85 sample plots, and 65 woody plant species were identified. Species with a frequency value below 5% in the vegetation data matrix were excluded and 56 species were included in the analysis. Additionally, environmental variables for each sample plot were obtained. Vegetation groups were obtained through clustering and two-way indicator species analysis methods during the vegetation classification stage. Subsequently, the most suitable discriminating group was identified using the multiple response permutation procedure (MRPP). It was observed that the clustering analysis based on Jaccard-Ward’s method yielded the most suitable discriminating group. Furthermore, positive and negative indicator species were identified through indicator species analysis. Spearman correlation analysis between the best discriminating group and environmental variables revealed that elevation, temperature index, and solar radiation index variables exhibited a positive relationship, while parent material, Bio1 and Bio15 variables showed a negative relationship. Similar results were obtained in canonical correspondence analysis (CCA) applied to interpret the relationships obtained through correlation analysis using ordination methods. According to CCA, elevation was positively associated with plant distributions and vegetation groups, while Bio1 and Bio15 variables were negatively associated.